FACTORS OF HUMAN RESOURCES POLICY FORMATION AT PHARMACEUTICAL INDUSTRY ENTERPRISES (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. In modern conditions, the effective functioning of the pharmaceutical industry, which provides the health care system, the supply of quality drugs to the population, performs a social function, has a significant impact on the development of the national economy. Such conditions require a study of the factors of personnel policy in the pharmaceutical industry, which will contribute to the effectiveness of employees and the enterprises competitiveness, improving the general population health.Goal of the article is to study the personnel policy formation factors of the pharmaceutical industry in the face of changes, challenges and threats.Methods. The article uses an abstract-logical, integrated approach, method of analysis and synthesis.Results. The article summarizes the scientific opinion on the characteristics and features of the pharmaceutical industry, the formation of personnel policy in a changing environment. Strategic groups of the pharmaceutical industry of Ukraine in the conditions of changes are defined. Models of influence of external and internal factors of enterprises personnel policy formation of pharmaceutical branch in the conditions of changes, challenges and threats are developed.The study allows to summarize scientific approaches to the nature, characteristics and features of the pharmaceutical industry, the personnel policy factors of the pharmaceutical industry, which will contribute to the employees and enterprises efficiency, improve public health.It was determined that the logistics, marketing and branding of medicinal products are of significant importance in the further successful development of the pharmaceutical industry. The introduction of a logistic approach to the management of the activities of enterprises in the pharmaceutical industry is one of the main trends at the current stage.